Effect of Age and Arteriosclerosis on the Response of Parkinsonian Patients to Levodopa. Issue 5786 (27th November 1971) - Godwin-Austen, R. B.; Bergmann, S.; Frears, C. C.
Abstract : Twenty-four patients with Parkinsonism were treated with levodopa for up to one year. Ten were aged under 65, 12 were aged 65 or over, and two were specifically included because they were considered to have arteriosclerotic Parkinsonism. These two patients showed no response to treatment. The 10 younger patients showed less clinical evidence of arteriosclerosis than the older ones, and responded significantly better to treatment with levodopa. Mean improvement was 61% in the younger group after 12 months' treatment and 28% in the older group. Improvement was greatest within three months of starting treatment. Abnormal movements which resulted from treatment with levodopa could be reduced with only slight loss of therapeutic benefit by the addition of tetrabenazine.